THE IMPACT OF SPIRITUAL LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT BMT IBAADURRAHMAN SUKABUMI - Nada Nurmughni Nabilatuzaman; Ahmad Maulidizen (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective – This study aims to examine the influence of spiritual leadership and organizational culture on employee performance at Baitul Maal wat Tamwil (BMT) Ibaadurrahman Sukabumi. The research focuses on understanding how these two factors, deeply rooted in Islamic values, impact the overall effectiveness and productivity of employees.Design/Methodology/Approach – The research employs a quantitative approach, using descriptive analysis, instrument tests, classical assumption tests, and hypothesis testing. Data were gathered through a Likert-scale questionnaire distributed to 41 respondents. The collected data were then analyzed using IBM SPSS and Microsoft Excel.Findings – That both spiritual leadership and organizational culture have a significant impact on employee performance, both individually and collectively. Specifically, it was found that spiritual leadership and organizational culture contribute positively to employee performance, with a simultaneous effect showing a combined contribution of 16.4%.Conclusion and Implications – The study concludes that spiritual leadership and organizational culture play critical roles in enhancing employee performance. These findings suggest that organizations, particularly Islamic financial institutions like BMT, should focus on fostering a strong organizational culture and spiritual leadership to boost productivity and employee well-being. The results provide practical implications for organizational development strategies in similar Islamic institutions. Keywords: Spiritual Leadership; Organizational Culture; Employee Performance; Islamic Financial Institutions; BMT Ibaadurrahman Sukabumi